The Role of Leadership Style on Evaluation Fairness - Efrizal Syofyan; Dovi Septiari; Riski Hernando (AKRUAL: JURNAL AKUNTANSI, 2021)
This study examines the effect of consideration of leadership style on evaluation fairness mediated by a combination of financial and non-financial performance measurements and levers of control. This study takes a population of employees who work at companies in the service, trade, and manufacturing sectors. The research location was conducted in the satellite area of Jakarta (Jabodetabek). We used a questionnaire distributed to respondents using the hand delivery systems technique. The data were analyzed and processed using structural equation modeling - partial least square (SEM-PLS) with the Warp-PLS software 3.0. This study shows that managers who use a consideration of leadership style directly affect the fairness of evaluation within the company. This study also shows that this relationship can be mediated by a combination of financial, non-financial performance measures and levers of control. Although, on a partial mediation basis. This research focuses on the relationship between the influence of leadership style consideration on evaluation justice. This study also looks at the role of mediation by a combination of financial, non-financial performance measurement and levers of control, namely: objective diagnostic, interactive objective, subjective diagnostic, and interactive subjective.